Plant and soil responses to ground-mounted solar panels in temperate agricultural systems - Fabio Carvalho; Hannah Montag; Laura Bentley; Radim Šarlej; Rosanne C Broyd; Hollie Blaydes; Marta Cattin; Miranda Burke; Abby Wallwork; Sammani Ramanayaka; Piran C L White; Stuart P Sharp; et al. (Environmental Research Letters)
In the move to decarbonise energy supplies to meet Net Zero targets, ground-mounted solar farms have proliferated around the world, with uncertain implications for hosting ecosystems. We provide some of the first evidence on the effects of ground-mounted solar panels on plant and soil properties in temperate agricultural systems. We sampled 32 solar farms in England and Wales in summer 2021. Plant cover and aboveground biomass, as well as soil nutrients and physiochemical properties, were quantified on land underneath solar panels, in the gaps between rows of solar arrays, and in control land (pasture) adjacent to three solar farms. Plant cover and aboveground biomass were significantly lower under solar panels than in the gaps between solar arrays and in pastures. Soil compaction was 14.4% and 15.5% higher underneath solar panels than in gaps and pastures, respectively. Soil organic carbon was 9% lower under solar panels than in gaps, while particulate organic matter was 29.1% and 23.6% lower under solar panels than in gaps and pastures, respectively. Soil mineral nitrogen was 30.5% higher under solar panels than in gaps, while soil (plant-available) phosphorus was approximately 60% higher in solar farm soils than in pasture soils. Reductions in solar radiation and changes to microclimate caused by solar panels may be driving lower plant productivity and growth, with consequences for nutrient cycling and soil properties. However, impacts must be considered in light of the previous land use and the total land area under solar panels, in the gaps between solar arrays, and around the margins of the solar farm. Our findings can inform solar farm design and management options (e.g. increase the proportion of land unaffected by solar panels, enhance plant cover under solar panels) to ensure the long-term provision of ecosystem services (e.g. soil carbon storage) within this fast-growing land use.